Insurance in the Eurasian Economic Union (EAEU) - U. T. Kadyrkulov; К. А. Ajekbarov (Путеводитель предпринимателя, 2021)
The paper considers the insurance sector of the EAEU countries is analyzed: Russia, Armenia, Kyrgyzstan, Kazakhstan and the Republic of Belarus. The development of insurance markets in the EAEU member states differ significantly. The lowest level of development of the insurance industry is characterized by Armenia and Kyrgyzstan, the highest level of development is in Russia. The paper also examines the restrictions on the reinsurance market in the EAEU countries.